Faktor Determinan Perilaku Deteksi Dini Kanker Payudara dengan SADARI pada WUS di Puskesmas Padang Pasir - Ginting, Desi Scorpinasari; Asri, Aswiyanti; Karmia, Hudila Rifa; Hilbertina, Noza; Meinapuri, Malinda; Hasmiwati, Hasmiwati (LPPM Hang Tuah Pekanbaru, 2025)
Breast cancer is the most commonly diagnosed cancer globally, accounting for nearly 12% of all cases. One in eight women worldwide is at risk of developing breast cancer. Regular Breast Self-Examination (BSE) is one of the most effective methods for early detection. This study aimed to identify the determinants of early breast cancer detection behavior through BSE among women of reproductive age. The study found significant associations between BSE behavior and several predisposing factors, including education level (p = 0.002), knowledge (p = 0.000), perception (p = 0.009), attitude (p = 0.024), and motivation (p = 0.016); enabling factor, namely information exposure (p = 0.000); and reinforcing factors, including family support (p = 0.001) and support from health workers (p = 0.027). Conversely, there was no significant association between social support and BSE behavior (p = 0.394). The study concludes that predisposing, enabling, and reinforcing factors are significantly associated with BSE behavior. Information exposure is identified as the most influential determinant of BSE behavior among women in the working area of Padang Pasir Public Health Center.